Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

We can define a representation of a Lie group and get the induced representation of the Lie algebra. Let $G$ act on $V$ and $W$, $\mathfrak{g}$ be the Lie algebra associated to $G$ and $X \in \mathfrak{g}$. Then the action on $V$ is defined as $\displaystyle X(v)=\left.\frac{d}{dt}\right|_{t=0}\gamma_t(v)$ where $\gamma_t$ is a path in $G$ with $\gamma'_0 = X$. Then: $$ \begin{align*} X(v \otimes w) & = \left.\frac{d}{dt}\right|_{t=0}\gamma_t(v)\otimes \gamma_t(w) \\ & \stackrel{?}{=}\left(\left.\frac{d}{dt}\right|_{t=0}\gamma_t(v)\right)\otimes w + v\otimes \left(\left.\frac{d}{dt}\right|_{t=0}\gamma_t(v)\right) \\ & = X(v)\otimes w + v \otimes x(w)\end{align*}$$ My question is: why does it split?

share|cite|improve this question
You are effectively taking the derivative of a product: $D(fg)=(Df)g+f(Dg)$ – Jyrki Lahtonen Aug 25 '11 at 20:40
I figured it out but it wont let me answer. I'll post it in 7 hours. Thanks for the edit Theo. – Sven Aug 25 '11 at 20:52
up vote 3 down vote accepted

$$ \begin{align*} X(v \otimes w) & = \left.\frac{d}{dt}\right|_{t=0}\gamma_t(v)\otimes \gamma_t(w) \\ & = \lim_{t \to 0} \,\,\, \frac{\gamma_t(v)\otimes \gamma_t(w)-v \otimes w}{t} \\ & = \lim_{t \to 0} \,\,\, \frac{\gamma_t(v)\otimes ( \gamma_t(w)-w+w)-v \otimes w}{t} \\ & = \lim_{t \to 0} \,\,\, \frac{\gamma_t(v)\otimes (\gamma_t(w)-w)+ \gamma_t(v)\otimes w-v \otimes w}{t} \\ & = \lim_{t \to 0} \,\,\, \frac{\gamma_t(v)\otimes (\gamma_t(w)-w)+ (\gamma_t(v)-v)\otimes w}{t} \\ & = \lim_{t \to 0} \,\,\, \frac{v \otimes (\gamma_t(w)-w)}{t}+ \lim_{t \to 0} \,\,\, \frac{(\gamma_t(v)-v)\otimes w}{t} \\ & =\left(\left.\frac{d}{dt}\right|_{t=0}\gamma_t(v)\right)\otimes w + v\otimes \left(\left.\frac{d}{dt}\right|_{t=0}\gamma_t(w)\right) \\ & = X(v)\otimes w + v \otimes X(w)\end{align*}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.